Synchronous metastatic squamous cell carcinoma to the colon and cervical lymph nodes from a carcinoma of unknown primary site: A case report - Ito, Homare (J Surg Case Rep, 2016)
Metastatic squamous cell carcinoma (SCC) from an unknown primary site to the colon has not been reported previously. A 75-year-old woman presented with a mass in the left submandibular region. Biopsy revealed a Class V lesion, but the histologic type was undetermined. Surgical resection of the left submandibular gland with cervical lymph node dissection was performed. However, SCC was seen in the lymph nodes only, with no tumor in the submandibular gland. Three months after surgery, computed tomography revealed that the preoperatively diagnosed lesion in the transverse colon had grown considerably. A laparoscopic right hemicolectomy was performed. Histological examination showed features of SCC, similar to the findings in the cervical lymph nodes. We report a rare case of synchronous metastatic SCC to the colon and cervical lymph nodes from a carcinoma of unknown primary site.